Childhood adversities and psychopathological outcomes - Infurna, Maria Rita (2015)
Maltreatment of children by their parents or other caregivers is widely spread, and can cause serious injury and severe long-term consequences. Child maltreatment encompasses any acts of commission or omission by a parent or other caregiver that result in harm, potential for harm, or threat of harm to a child or adolescent (usually interpreted as up to 18 years of age), even if harm is not the intended result. In the past two decades, four forms of maltreatment have been increasingly recognised: physical abuse; sexual abuse; psychological abuse, sometimes referred to as emotional abuse; and neglect. Research from high-income countries revealed that 4–16% of children experienced severe parental violence, 15–30% of girls and 5–15% of boys experienced sexual abuse, and one in ten children was neglected. Self-report studies from the UK and the US showed that 8–9% of women and about 4% of men reported exposure to severe psychological abuse during childhood. Childhood maltreatment has unique and important implications since it can exert negative influences on sensitive developmental periods for emotional, behavioural, cognitive, and social domains; thereby, interrupt healthy development and lead to an increased risk for the development of psychopathology. Indeed, there is a large body of evidence that exposure to childhood maltreatment is a robust predictor of later psychiatric disorder, including mood disorders, anxiety disorders, eating disorders, substance use disorders, posttraumatic stress disorder (PTSD), and personality disorders. Thus, there is increasing interest in deepen the understanding on how and under which circumstances childhood adversity leads to psychiatric disorders; and in identifying different factors that may be associated with specific forms of mental suffering. Theoretical models have posited that specific types of childhood adversity, such as physical abuse, sexual abuse or psychological abuse, may be uniquely related to specific psychiatric outcomes. Unfortunately, studies among youth and adult samples suggest that, while exposure to early adversity is associated with increased risk for psychiatric disorder, the influence of specific types of childhood maltreatment on different mental disorder outcomes remains controversial. The aim of present thesis was a deep examination of the potential psychopathological outcomes related to childhood adversities. In particular, the specific role of different kinds of childhood maltreatment (e.g., physical, sexual, and emotional abuse) and of familial or social factors (e.g., parental bonding, family functioning, social support) on different mental disorders (e.g. borderline personality disorders, depression, etc.) was examined. For this purpose, the present work is articulated in three separate studies, each of which has analyzed specific aspects of the main topic. In particular, Study 1 has focused on the specific associations of childhood maltreatment, parental bonding and family functioning in female adolescents with borderline personality disorder (BPD) compared with female adolescents with others psychiatric conditions. Study 2 sought to investigate the specific effect of environmental factors on mental health outcomes of early-maltreated adults, by comparing a group of mixed clinical participants (CG) with childhood experiences of abuse and neglect with a healthy group (HG) with similar patterns of experiences. Finally, Study 3 used a meta-analytic approach to assess the specific influence of different types of maltreatment on depression outcome in adults and adolescents. In addition to the general topic, the recurrent theme of the three studies was the specific assessment measure that was used to detect and classify early experiences of childhood adversity: the Childhood Experiences of Care and Abuse (CECA), interview or questionnaire version (Bifulco, Bernazzani, Moran, & Jacobs, 2005; Bifulco, Brown, & Harris, 1994). This measure is considered the current ‘gold standard’ for the assessment of adverse childhood experiences in the international research field. The findings of the present three studies revealed interesting insights allowing better understanding of the specific influence of different types of childhood adversity on specific mental health outcomes. The results from Study 1 and 3 clearly showed that the more “silent” forms of maltreatment such as psychological abuse, antipathy and neglect might have a decisive role on development of psychopathological outcomes. Given that a broad range of experiences is subsumed under the term “adversity,” future research and clinical assessment needs to be comprehensive and assess a large range of early maltreatment forms. Exhaustive, complex, and reliable assessment tools that are able to detect the large variety of negative experiences and include key dimensions of these experiences such as type, severity, chronicity, and timing should support these assessments. Finally, those identified with a history of early adversity may be candidates for more intensive psychiatric and psychotherapeutic treatments. As our understanding of the differential effects of adversity develops, treatments may be individually tailored to the type and timing of exposure. As demonstrated in Study 2, psychological resilience derived from positive social support to those who were able to survive early life adversity without psychopathological development. In case of a critical family environment, support from outside may thus potentially attenuate the effect of adversity exposure on the subsequent risk for psychiatric disorder. Community-based preventive interventions that improve either the quality of children’s family life or alternatively the support of their respective neighbourhood environments may have substantial long-term benefits by reducing the incidence of psychiatric disorders in the general population. Some periods of vulnerability have also been highlighted in this research. Indeed, results from Study 3 showed that adolescents were more affected by childhood maltreatment than adults in terms of their risk for major depressive disorder. Theorists have argued that exposure to adversity during the critical developmental periods of late childhood and early adolescence may confer high vulnerability to particular forms of psychiatric disorders, perhaps owing to the rapid brain development that occurs during these ages. Thus, the transition to puberty may be a critical developmental period, which carries increased risk for particular forms of psychiatric disorders in case of a disturbing and non-supportive environment. Further research is needed to identify the precise critical periods and the forms of adversity most damaging at each period. Longitudinal designs might offer significant advantages for examining differential effects of early adversity by age of exposure, and thus for identifying critical periods in human development that confer heightened risk for psychiatric disorders in later life.
Keywords: Hochschulschrift; Psychopathologie; Notlage; Kind